Retail policy and local development in metropolitan space: Some lessons from the case of Tres Cantos (Madrid) new town - Antonio Moreno Jimenez (European Regional Science Association (ERSA), 1998)
Urban development, as comprehensive concept, involves a wide set of components, and it would imply a reasonably well balanced growth of differents urban functions and activities. The strong spatial competition between firms and localities in metropolitan areas yields unequal spatial impacts on the growth of retail activities. An usual scenery in western suburban areas is the presence of great retail facilities dominating the surrounding market. This situation negatively affects to little and lower-medium settlements that, in this way, play a dominated role, seen as undesirable by local agents and provoking emergent policies. Grounded on this basis this paper tackles the case of a lower medium new town located near Madrid (Tres Cantos), where the local government and retail organisations have reacted against its dominated role and have promoted a set of measures to overcome the problems detected, mainly the local consumer leakeage, the limited success or failure of new retail firms and, in a wider sense, the underdevelopment of the local retail sector. The study describes the main findings of a wider report conducted to evaluate the implemented measures, its effectiveness and the local market agents' valuation. This experience also illustrates the problems of objective setting and policy implementation, when the public and the private sector participate in a joint decision. Keywords: new town development, retail system, urban retail policy Suitable for Conference Themes: D (Metropolitan processes and policies) or parhaps, H (Services, small enterprises ....)
Keywords: 330